2013
DOI: 10.1002/14651858.cd003878.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for replacing missing teeth: different times for loading dental implants

Abstract: Overall there was no convincing evidence of a clinically important difference in prosthesis failure, implant failure, or bone loss associated with different loading times of implants. More well-designed RCTs are needed and should be reported according to the CONSORT guidelines (www.consort-statement.org/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
266
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(284 citation statements)
references
References 60 publications
14
266
1
3
Order By: Relevance
“…In a prospective 5-year follow-up cohort study, 13 implants after 4 years of loading. 18 The survival rate and success rate was 96.7% and 80%, respectively. Our present study showed similar results, which reported 3-year total survival rate 95.8% and a mean MBLC of 0.07 6 0.49 mm.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a prospective 5-year follow-up cohort study, 13 implants after 4 years of loading. 18 The survival rate and success rate was 96.7% and 80%, respectively. Our present study showed similar results, which reported 3-year total survival rate 95.8% and a mean MBLC of 0.07 6 0.49 mm.…”
Section: Discussionmentioning
confidence: 91%
“…Since then, several studies have confirmed that using early loading protocols for dental implants can have high survival rates and good clinical outcomes. [14][15][16][17][18] However, whether the early loading protocol can be used routinely remains unclear. This is particularly so in the posterior jaws, where the occlusal forces are much higher than in the anterior jaws; or with the short implants, which have less part engaged in bone.…”
mentioning
confidence: 99%
“…As a result of these findings, many authors have recommended the routine use of connective tissue graft to thicken the labial soft tissue to .2 mm. 12,13 In particular, the recession of the facial mucosa is the main complication observed with immediate implants. 1,[14][15][16][17][18][19][20] Implant placement in aesthetic areas (ie, anterior maxillary teeth) is challenging, 21 and adequate labial or buccal bone thickness seems to be critical to prevent future bone dehiscence and marginal recession.…”
mentioning
confidence: 99%
“…[1][2][3] Immediate loading is defined as 'functional loading of an implant within one week of its placement. 4 This loading protocol of implants in edentulous and partially dentate arches has shown equally successful outcomes as those loaded after a delay of 2-3 months. [5][6][7] Bisphosphonate are one of the most common antiresorptive drugs being prescribed for certain bone diseases, including osteoporosis.…”
Section: Introductionmentioning
confidence: 90%